Stearoyl-CoA desaturase 1 regulates malignant progression of cervical cancer cells. Issue 5 (2nd May 2022) - Wang, Lingling; Ye, Guoliu; Wang, Yan; Wang, Caizhi
ABSTRACT: The primary regulatory gene for fatty acid synthesis, stearoyl-CoA desaturase 1 (SCD1), has been linked to the progression of several malignancies. Its role in cervical cancer remains unclear till now. This paper aimed to explore the role and mechanism of SCD1 in cervical cancer. The GEPIA database was used to perform a bioinformatics analysis of the role of SCD1 in cervical cancer staging and prognosis. The influences of SCD1 knockdown on cell proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) progress were then investigated. Following transcription factor Kruppel like factor 9 (KLF9) was discovered to be negatively correlated with SCD1, the regulatory role of KLF9 in the effects of SCD1 on cervical cancer cells and the signaling pathway was evaluated. According to the GEPIA database, SCD1 level was associated with the cervical cancer stage, the overall survival level, and the disease-free survival level. Cell proliferation, migration, invasion, and EMT progress were all hindered when its expression was knocked down. Novelty, KLF9 reversed the effects of SCD1 on cells, as well as the Akt/glycogen synthase kinase 3β (GSK3β) signaling pathway. Together, SCD1 was negatively regulated by KLF9 and it activated the Akt/GSK3β signaling pathway to promote the malignant progression of cervical cancer cells. Developing SCD1 inhibitors offers novel ideas for the biological treatment of cervical cancer. Graphic abstract: uf0001